Integration of the Technology Acceptance Model and Flow Experience in Online Travel Agent Repurchase Intention - Velika Ibrahim; Surya Setyawan (SAFE-Network, 2026)
This study aims to analyze the effect of Perceived Usefulness and Perceived Ease of Use on Flow Experience and its impact on Rebooking Intention. This study adopts a quantitative approach with a total of 194 respondents. The data were analyzed using SEM-PLS. The results indicate that Perceived Usefulness has a significant effect on Flow Experience, while Perceived Ease of Use does not significantly affect Flow Experience. Furthermore, Flow Experience has a significant effect on Rebooking Intention. However, both Perceived Usefulness and Perceived Ease of Use do not significantly affect Rebooking Intention. These findings suggest that user experience plays a more important role in influencing rebooking intention compared to cognitive factors such as perceived usefulness and ease of use. Therefore, application providers should enhance the quality of user experience to increase user engagement and loyalty in the context of Online Travel Agents.